GENERAL CONTROL NONREPRESSIBLE4 Degrades 14-3-3 and the RIN4 Complex to Regulate Stomatal Aperture with Implications on Nonhost Disease Resistance and Drought Tolerance. Issue 9 (30th August 2017) - Kaundal, Amita; Ramu, Vemanna S.; Oh, Sunhee; Lee, Seonghee; Pant, Bikram; Lee, Hee-Kyung; Rojas, Clemencia M.; Senthil-Kumar, Muthappa; Mysore, Kirankumar S.
Abstract : GCN4, an AAA + -ATPase family protein, is a novel player in stomatal aperture regulation that can affect plant immunity and abiotic stress. Abstract: Plants have complex and adaptive innate immune responses against pathogen infections. Stomata are key entry points for many plant pathogens. Both pathogens and plants regulate stomatal aperture for pathogen entry and defense, respectively. Not all plant proteins involved in stomatal aperture regulation have been identified. Here, we report GENERAL CONTROL NONREPRESSIBLE4 (GCN4), an AAA + -ATPase family protein, as one of the key proteins regulating stomatal aperture during biotic and abiotic stress. Silencing of GCN4 in Nicotiana benthamiana and Arabidopsis thaliana compromises host and nonhost disease resistance due to open stomata during pathogen infection. AtGCN4 overexpression plants have reduced H + -ATPase activity, stomata that are less responsive to pathogen virulence factors such as coronatine (phytotoxin produced by the bacterium Pseudomonas syringae ) or fusicoccin (a fungal toxin produced by the fungus Fusicoccum amygdali ), reduced pathogen entry, and enhanced drought tolerance. This study also demonstrates that AtGCN4 interacts with RIN4 and 14-3-3 proteins and suggests that GCN4 degrades RIN4 and 14-3-3 proteins via a proteasome-mediated pathway and thereby reduces the activity of the plasma membrane H + -ATPase complex, thus reducing proton pump activity to close stomata.